Portal web para la Cooperativa de Ahorro y Crédito de la Pequeña Empresa CACPE Loja con módulos de simulación de créditos y precalificación de socios, implementando niveles de seguridad HTTPS mediante el lenguaje de programación ASP.NET. - Jara Cabrera, Freddy Vinicio (2012)
The Web Portal of the Savings and Credit Cooperative Small Business, CACPE-Loja, has as main purpose to improve the corporate image and to publish the products and services offered by the company, improving communication with the general public, through the online inquiry service, credit simulators, currency converter and updated information about the CACPE. The Web portal was developed following the model of software architecture MVC (Model View Controller) covering essentially: Consultations, management, and entry through a secure communication channel provided by SSL and HTTPS using a digital certificate test provided by the tool X509 BUILDER and cryptographic algorithms such as SHA1 to maintain the confidentiality, authenticity and integrity of data. Standards were also used CSS, JavaScript, jQuery, Ajax, Microsoft Enterprise Library and controls Net that allow the portal to be compatible between different operating systems and browsers resident on PCs or mobile devices of last generation. Configured and customized the Web Mail of the cooperative, which has as main objective to allow employees to access their email from any machine or mobile device that is connected to the internet. It also offers a phone directory with security levels that is exclusively for internal use. As noted above, this Web Portal becomes a strategic tool to increase significantly the group of partners, a situation reflected in the economic balances of the CACPE. Finally with the completion of the development of this thesis, I present conclusions and recommendations.